2010
DOI: 10.3109/07853890.2010.531757
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in BCMO1 and CD36 are associated with plasma lutein concentrations and macular pigment optical density in humans

Abstract: these results suggest that BCMO1 and CD36 are implicated in plasma and retina concentrations of lutein and that genetic variants in these genes can modulate blood and retina concentrations of lutein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 56 publications
1
61
0
Order By: Relevance
“…Both dietary factors (17) and genetic variations between individuals (18) have been proposed to explain this phenomenon. In support of the latter factor, recent studies have shown that blood and tissue concentrations of lutein are associated with genetic polymorphisms (16,19,20).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Both dietary factors (17) and genetic variations between individuals (18) have been proposed to explain this phenomenon. In support of the latter factor, recent studies have shown that blood and tissue concentrations of lutein are associated with genetic polymorphisms (16,19,20).…”
Section: Introductionmentioning
confidence: 89%
“…PLS is a multivariate statistical tool often used for chemometric (38) and spectrometric modeling and has recently been applied to SNP-based predictions by our group (31) and other researchers (19,31,39,40). Because of the large number of SNPs compared with the low number of subjects and the multicollinearity between SNPs, PLS regression was chosen to identify SNPs (of the 1785 candidate SNPs) that were predictive of the postprandial chylomicron lutein response according to their variable importance in the projection (VIP) value.…”
Section: Statistics: Pls Regressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in the BCMO1 gene were associated with circulating concentrations of α and β carotenes, lycopene, lutein and zeaxanthin. These results suggest that the variation of BCMO1 gene can affect the status of carotenoids and therefore the answer to supplement [32].…”
Section: Genetic Determinants Of Carotenoids Statusmentioning
confidence: 95%